High-resolution spatial transcriptomics in fixed tissue using a cost-effective PCL-seq workflow - Dong, Xue; Hu, Mengzhu; Cui, Xiaonan; Zhou, Wenjian; Cai, Jingtao; Mao, Guangyao; Shi, Weiyang

(untitled) (Genome Research, 2025)
The spatial heterogeneity of gene expression has driven the development of diverse spatial transcriptomics technologies. Here, we present photocleavage and ligation sequencing (PCL-seq), a spatial indexing method utilizing a light-controlled DNA labeling strategy applied to tissue sections. PCL-seq employs photocleavable oligonucleotides and ligation adapters to construct transcriptional profiles of specific regions of interest (ROIs) designated via microscopically controlled photo-illumination. In frozen mouse embryos, PCL-seq generates spatially aligned gene expression matrices and produces high-quality data, detecting approximately 170,000 unique molecular identifiers (UMIs) and 8600 genes (illumination diameter = 100 µm). Moreover, PCL-seq is compatible with formalin-fixed paraffin-embedded (FFPE) tissues, successfully identifying thousands of differentially enriched transcripts in the digits and vertebrae of mouse embryo FFPE sections. Additionally, PCL-seq achieves subcellular resolution, as demonstrated by differential expression profiling between nuclear and cytoplasmic compartments. These characteristics establish PCL-seq as an accessible and versatile workflow for spatial transcriptomic analyses in both frozen and FFPE tissues with subcellular resolution.